2022
DOI: 10.1186/s40337-022-00680-0
|View full text |Cite
|
Sign up to set email alerts
|

Food addiction, orthorexia nervosa and dietary diversity among Bangladeshi university students: a large online survey during the COVID-19 pandemic

Abstract: Purpose Maladaptive eating behaviors like food addiction (FA) are common among students, and orthorexia nervosa (ON) is being evaluated as a new condition among eating disorders (EDs). Moreover, dietary diversity (DD) is recognized as an important component of a healthy diet. Thus, the current study sought to examine the prevalence of ON and FA as well as the factors associated with ON, FA, and DD among university students in Bangladesh during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 76 publications
3
18
0
Order By: Relevance
“…It is worth noting that the second phase of our study was conducted during the COVID-19 pandemic, which could also have affected the students’ eating attitudes and behaviors. Another study conducted during the COVID-19 pandemic showed that students who had a higher prevalence of OB consumed more legumes, nuts and seeds, dark green leafy vegetables, fruits and vegetables rich in vitamin A, milk and milk products [ 54 ]. A well-balanced and varied diet is important to provide a healthy immune system, which is especially important during the pandemic [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the second phase of our study was conducted during the COVID-19 pandemic, which could also have affected the students’ eating attitudes and behaviors. Another study conducted during the COVID-19 pandemic showed that students who had a higher prevalence of OB consumed more legumes, nuts and seeds, dark green leafy vegetables, fruits and vegetables rich in vitamin A, milk and milk products [ 54 ]. A well-balanced and varied diet is important to provide a healthy immune system, which is especially important during the pandemic [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted during the COVID-19 pandemic showed that students who had a higher prevalence of OB consumed more legumes, nuts and seeds, dark green leafy vegetables, fruits and vegetables rich in vitamin A, milk and milk products [ 54 ]. A well-balanced and varied diet is important to provide a healthy immune system, which is especially important during the pandemic [ 54 , 55 ]. The fear and stress caused by the pandemic may lead to an increase in healthy eating obsession [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have read the article entitled “Food addiction, orthorexia nervosa and dietary diversity among Bangladeshi university students: a large online survey during the COVID-19 pandemic” published by Sultana et al [ 1 ] in the prestigious journal. Sultana et al conducted an exciting study that explored the prevalences of orthorexia nervosa and food addiction (FA) and their associations with dietary diversity in university students in Bangladesh during the COVID-19 pandemic.…”
Section: Main Textmentioning
confidence: 99%
“…Globally, during the pandemic period, increases were reported in multiple mental health conditions among adolescents, including anxiety, depression, trauma, grief, suicidal behaviors, and substance [24,25]. In Bangladesh, several studies investigating COVID-19 impacts on mental health were conducted [26][27][28][29][30][31][32][33][34][35][36][37]. However, very few studies looked at mental health in adolescents and instead focused on specific groups (university students, healthcare workers) or populations (slum dwellers, general population).…”
Section: Introductionmentioning
confidence: 99%